Preparation and Performance of Self-healing Polyurethane with Reversible Dual Cross-linked Networks - Yong WANG; Ruofan LIU; Yushun JIN; Wei DING; Yibo WU (Pige Kexue Yu Gongcheng)
A series of double-crosslinked polyurethane elastomers were prepared by physically crosslinking a single-crosslinked network of reversible disulfide-bonded polymers and a single-crosslinked network of reversible Fe3+-coordination-bonded polymers. Through this, reversible double-crosslinked network interlocked self-repairing polyurethane materials were obtained and named as FSN. This kind of material utilized the disulfide bonds in the reversible double bond network and the metal coordination bonds in the Fe3+-coordination-bonded network to interpenetrate and interlock, thus forming a reversible double crosslinked network self-repairing elastomer material with the synergistic action of the two single crosslinked networks. The self-healing ability and mechanical properties of the double crosslinked networks were investigated, and the experimental results showed that the mechanical stress of the FSN network reached 3.5 MPa, and the self-healing efficiency of the polymer was more than 80%. This result demonstrates that there is a synergistic effect between the two single-crosslinked networks, which results in a significant increase in the mechanical properties and self-healing ability of FSN over a single reversible polymer network.